Three Years Experience in the Management of Uterine Rupture at Al-Battool Teaching Hospital Mosul-Iraq - Sarsam, Samar D. (AL-Kindy College Medical Journal, 2008)
Background: Ruptured uterus is a catastrophic event to both mother and her fetus. Apart from maternal and fetal mortality rates, the incidence of rupture of uterus is often taken as an index of the standard of obstetric care. Objective: To determine the frequency, causes, management outcome of ruptured uterus at Al Batool maternity hospital. Method: The study was conducted in the department of obstetrics and gynecology at Al Batool maternity hospital Mosul-Iraq over a period of three years from October 1st 2002 to August 30th 2005. All the cases of uterine rupture presented during the study period were recorded and managed in the department. Data was recorded on designed forms. Results: Thirty nine cases of ruptured uterus out of 44539 deliveries were registered, the incidence was 0.087%. Age ranged from 15 to45 years. The majority of the patients were grandmultipara (Para 5 and above), but 7 of the patients were nulliparous women (17.94%). 26 ruptures (66.66%) occurred in unscarred uterus and 13 ruptures (33.33%) occurred in scarred uterus, cephalopelvic disproportion and obstructed labor were the cause of rupture in 11 cases (28.2%), in addition to the mentioned causes 11 cases of the uterine ruptures we registered in our study (28.2%) were mishandled by the traditional birth attendants, and in 14 cases (35.89%) there was injudicious use of oxytocin. We had three maternal deaths (7.69%) out of 39 patients, and only 10 fetuses out of 39(25.64%) were alive. Conclusion: Rupture uterus is still an important cause of maternal and perinatal mortality and morbidity in Iraq, it is not always suspected, and hence increased vigilance is vital. Further studies may help in the development of preventive strategies and ensure prompt management to reduce maternal and perinatal mortality and morbidity